2001
DOI: 10.1176/appi.ajp.158.5.718
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Locus on Chromosome 1 That Influences Vulnerability to Alcoholism and Affective Disorder

Abstract: The results suggest that a gene or genes on chromosome 1 may predispose some individuals to alcoholism and others to depression (which may be alcohol induced). Loci on other chromosomes may also be of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
126
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 20 publications
9
126
3
2
Order By: Relevance
“…A second region which includes markers D1S196 and D1S2878 is within 1 cM of the gene for an aldehyde dehydrogenase (ALDH9), an enzyme that catalyzes gamma aminobutylaldehyde to GABA. The region near D1S230 has previously been reported by the COGA group to give evidence for linkage Foroud et al, 2000;Nurnberger et al, 2001;Dick et al, 2002]. In the present study, multipoint linkage analysis showed a LOD value of 3.46 (P = 0.002) for marker D1S196 [181.49 cM Marshfield] and a similar LOD value (3.45) at the adjacent marker D1S2878 using a three covariate model that included age, gender, and constraint.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…A second region which includes markers D1S196 and D1S2878 is within 1 cM of the gene for an aldehyde dehydrogenase (ALDH9), an enzyme that catalyzes gamma aminobutylaldehyde to GABA. The region near D1S230 has previously been reported by the COGA group to give evidence for linkage Foroud et al, 2000;Nurnberger et al, 2001;Dick et al, 2002]. In the present study, multipoint linkage analysis showed a LOD value of 3.46 (P = 0.002) for marker D1S196 [181.49 cM Marshfield] and a similar LOD value (3.45) at the adjacent marker D1S2878 using a three covariate model that included age, gender, and constraint.…”
Section: Discussionsupporting
confidence: 72%
“…Reanalysis of the region containing D1S1588 by COGA investigators [Nurnberger et al, 2001;Dick et al, 2002] supported the earlier findings of Reich et al [1998] and Foroud et al [2000]. Nurnberger et al [2001] using phenotypes that included, alternatively, alcoholism with comorbid depression, or alcoholism or depression alone obtained LOD scores of 5.12, 1.52, and 4.66 at marker D1S1588 in initial, replication, and combined data sets, respectively.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The human CNR2 gene is located on chromosomes 1p36, nearby where only one report has indicated a broad and weak linkage to alcoholism, 31 although common linkage area was reported around chromosome 1p31, not very close to CNR2 locus. 32 Because our genetics data indicated that CNR2 has a moderate effect on human alcoholism and our mouse studies revealed the contributions of non genetic factors related to development of alcohol preference, it is likely that reinforcement of alcohol preference/addiction and stress may also influence endocannabinoids regulation that alters Cnr2 gene/protein expression in CNS. It is also likely that CNR2 contributes to initiation and development of alcoholism during periods of vulnerability owing to stress.…”
Section: Discussionmentioning
confidence: 90%